Emotional Empathic Responses to Dynamic Negative Affective Stimuli Is Gender-Dependent - Kuypers, Kim P. C. (Front Psychol, 2017)
Empathy entails the ability to recognize emotional states in others and feel for them. Since empathy does not take place in a static setting, paradigms utilizing more naturalistic, dynamic stimuli instead of static stimuli are perhaps more suited to grasp the origin of this highly complex social skill. The study was set up to test the effect of stimulus dynamics and gender on empathic responses. Participants were 80 healthy volunteers (N = 40 males) aged 22.5 years on average. Behavioral empathy was tested with the multifaceted empathy test, including static emotional stimuli, and the multidimensional movie empathy test (MMET), including dynamic stimuli. Findings showed emotional empathy (EE) responses were higher to negative emotional stimuli in both tasks, i.e., using static as well as dynamic stimuli. Interestingly a gender-dependent response was only seen in the MMET using dynamic stimuli. It was shown that females felt more aroused and were more concerned with people in negative affective states. It was concluded that the MMET is suited to study gender differences in EE.